Maps, imaginary and environmental memory in Argentina - Hollman, Verônica (Geografares, 2014)
While research on social ideas of nature focused on the discursive side of environmental rhetoric during the last decade of the twentieth century, the visual turn has introduced the analysis of its visual facet: the study of the visual representation of nature in photographs, films, paintings and media among many other image-based media. However, scarce attention has received the study of what is provoked by environmental images as well as how they shape our imagination and memory of environmental issues. Based on the analysis of mental maps created by 215 subjects -all of them students of the undergraduate programs of the Faculty of Humanities at Universidad Nacional del Centro de la Provincia de Buenos Aires Province (Argentina) in 2013- as the starting point to identify images that have become constitutive environmental memory, the article discusses the role of environmental images in shaping both our ways of looking to nature and our understanding of environmental issues.Keywords: maps; environmental memory; visual culture.